Emerging theory of sensitization in post-stroke muscle spasticity - Areerat Suputtitada (Frontiers Media S.A., 2023)
Spasticity, characterized by a velocity-dependent increase in muscle tone and exaggerated reflexes, is a common complication in individuals with upper motor neuron syndrome, such as stroke survivors. Sensitization, the heightened responsiveness of the nervous system to sensory stimuli, has emerged as a potential cause of spasticity. This perspective article explores three emerging treatments targeting sensitization. Recent studies have investigated novel treatment modalities for spasticity, including Extracorporeal Shockwave Therapy (ESWT), repetitive peripheral magnetic stimulation (rPMS), and needling. ESWT has shown promising results in reducing spasticity in both the upper and lower extremities, potentially through mechanisms such as nitric oxide production, rheological property changes, and neuromuscular transmission dysfunction. rPMS offers a non-invasive approach that may reduce spasticity by increasing sensory input, enhancing cortical activation, and exerting tissue-softening effects. Needling has also demonstrated positive effects on spasticity reduction. The high heterogeneity observed indicates the need for more rigorous research to confirm these findings. Recently, mechanical needling and sterile water injection invented by the author is also promising for reducing spasticity through removing sensitization. In conclusion, the emerging treatment options discussed in this perspective article provide promising avenues for addressing sensitization in spasticity and improving motor function. However, further research is needed to validate their findings, optimize treatment protocols, and investigate their long-term effects on motor recovery and overall quality of life in individuals with spasticity.